Pengaruh Promosi, Kualitas Produk dan Harga terhadap Keputusan Pembelian pada Keranjang Sayur Online - Danil Indriyani; Agustin Riyan Pratiwi; Shella Rizqi Amelia (Jurnal Bisnis dan Kewirausahaan, 2024)
Bakul Sayur Online Purbalingga Online is an online shop that has a problem phenomenon. Based on interviews and data obtained, there are still phenomena related to minimal promotion, the quality of vegetable products whose durability is still not good. Based on the research gap from research conducted by Melati (2021), the price variable was found to be the answer to the limitations of this research. This research aims to find out the extent to which promotion, product quality and price influence purchasing decisions. This research uses quantitative methods. The population used in this research was a sample of 95 respondents. The sampling technique uses random sampling technique. The analysis used in this research used SPSS version 26.0. The results of this research show that promotions have a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on purchasing decisions. Price has a negative and significant effect on purchasing decisions. Apart from that, promotion, product quality and price simultaneously influence purchasing decisions. The coefficient of determination is 0.31, meaning that the independent variable has an influence of 31% on the independent variable, namely purchasing decisions, and the remaining 69% is influenced by other factors not examined in this research.